Mangsuk as a Learning Space of Mother tongue in the Yamphu Community of Nepal: An auto/ethnographic inquiry - Rai Yamphu, Prabin (Kirat Pragya किरात प्रज्ञा, 2025)
Nepal is rich in lingual, cultural, geographical and social diversities. It has 142 castes/ethnicity and 124 languages according to the population census of 2021.Yamphu language is one of the endangered languages used by older generations of people living in the country’s eastern hills. Yamphu people are a separate lingual and cultural group under the “Rai” ethnonym within the Kirant community. As an indigenous community, they have been adopting Mundhum as an oral tradition of knowledge transfer since the centuries. In this context, Mangsuk incorporates Mundhum and its several practices. Mansuk is rooted deeply as a ritual, an institution, and indigenous learning system in Yamphu community. This paper portrays how the Mangsuk facilitates the key role to learn mother tongue in the Yamphu community. I presented my lived experiences and my Yamphu community’s voices as research text in which I followed auto/ethnography as a research method. I employed indigenous knowledge and transformative learning theory as theoretical frames. I explored Mangusk tradition in terms of learning the mother tongue, by interacting with the ritual priests and other community members in a hilly settlement in Ilam district, Nepal. I found that Mangsuk is an important space of learning the mother tongue of the Yamphu community, which needs to be acknowledged by current formal educational system. This research has implications for educational policy makers, linguistic planners, and indigenous activists to affirmatively raise the strengths of indigenous cultures, rights, and dignity.